KONTRAK KAPITASI DALAM HUKUM KONTRAK INDONESIA - Andini Aprilia Wardhani; Erni Agustin (Media Iuris, 2018)
The existence of Act No. 3 of 1992 on Social Security of Labor which regulates that a company is required to provide social security, one of them by providing health insurance for its workers. One form of health insurance provided by the company to its employees is through a healthcare contract, made between the company and the hospital generally referred to as the capitation contract. However, until now there has been no legislation regulating the capitation contract so that the question arises about the validity, characteristics, and implementation of the capitation contract itself. This article aims to examine the characteristics, the validity, and the implementation of capitation contract in Indonesia. Specifically, this type of capitation contract has not been regulated in Indonesian legislation. The parties to the capitation contract are hospitals as providers of healthcare services and companies as recipients of healthcare services. Payments in capitation contracts are fixed and made regularly provided by the recipients of health care services. Capitation contracts are included in contracts that are beneficial to the third parties. Implementation of captation contract in Indonesia refers to the prevailing laws and regulations in Indonesia and should not be contradictory to the regulations such as Social Security of Labor, Health Law and Hospital Law.